THE EFFECT OF PRICE AND PROMOTION ON INCREASING SALES AT THE EAST COFFEE PANGALENGAN - Rindi Tri Utami; Dadang Munandar (PT. Jurnal Center Indonesia Publisher, 2026)
The coffee shop industry in Indonesia continues to grow alongside changes in consumer lifestyle, particularly in tourism areas such as Pangalengan, Bandung Regency. Despite having strong market potential, sales performance at The East Coffee has shown noticeable fluctuations. Sales records from November 2024 to October 2025 indicate that monthly revenue ranged from IDR 6,084,522 in March 2025 to IDR 10,726,758 in July 2025. This condition suggests that sales performance has not been stable and highlights the need to evaluate marketing strategies, especially pricing and promotion. This study aims to examine the effect of price and promotion on sales growth at The East Coffee Pangalengan. A quantitative approach with descriptive and verification methods was applied. The sample consisted of 72 respondents, selected using incidental sampling. Data were collected through structured questionnaires and analyzed using multiple linear regression with SPSS, including validity and reliability tests, classical assumption tests, t-tests, F-tests, and coefficient of determination analysis. The descriptive results show that Price (76%), Promotion (80%), and Sales Growth (74%) are perceived positively and categorized as strong. Verification analysis reveals that price has a positive and significant effect on sales growth (t = 8.017; Sig. = 0.000; β = 0.856), while promotion has a significant but negative effect (t = −2.346; Sig. = 0.022; β = −0.329). Simultaneously, price and promotion significantly influence sales growth (F = 90.421; Sig. = 0.000), with the model explaining 72.4% of the variance in sales growth (R² = 0.724). These findings indicate that sales growth at The East Coffee is more strongly driven by appropriate pricing perceptions, while promotional strategies require improvement to achieve more consistent and sustainable sales performance.